Exploring runoff variation and attribution analysis based on the SWAT model and the Budyko framework in the Huangyang River of the Northwest Inland Region, China - Li, Wenxin; Chen, Peng; Li, Kuijing; Shu, Heping (Frontiers in Water, 2025)
The ecological degradation and groundwater level decline caused by runoff reduction in arid inland river basins are becoming increasingly severe under the dual pressures of global climate change and human activities. The Huangyang River was selected as the study area, the Mann-Kendall mutation test and sliding T-test method were used to identify runoff mutation points. The transfer matrix method and sensitivity analysis were applied to clarify the relationship between land use change and runoff variation. The Budyko water–heat coupling theory and the SWAT model were carried out to explore the driving mechanisms of climate change and human activities on runoff. The results showed that the annual runoff decreased significantly at a rate of 0.042 × 108 m3·a−1 (p < 0.05), with 1991 being the mutation point. From the baseline period to the change period, runoff decreased by 0.15 × 108 m3. The attribution analysis of the SWAT model and the Budyko hypothesis consistently indicates that human activities were the main drivers of runoff changes, with human activities contributing 69.52 and 68.84%, and climate change contributing 30.48 and 31.16%, respectively, among them, the contribution rate of land use was 10.70%, and that of other human activities was 58.82%. This confirms that human activities have significantly altered the hydrological processes of the basin. The findings provide theoretical support for the sustainable development of inland river basins.